2019
DOI: 10.1027/1614-0001/a000272
|View full text |Cite
|
Sign up to set email alerts
|

Sandbagging and the Self

Abstract: Abstract. Sandbagging – a self-presentation strategy defined by feigned performance or false claims of inability – has been associated with lower self-esteem. The purpose of this study was to investigate whether narcissism explains the relationship between sandbagging and self-esteem. College students ( N = 813) completed a survey. Grandiose and vulnerable narcissism explained variance in sandbagging beyond what was explained by self-esteem. When grandiose or vulnerable narcissism was included, the relationshi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 28 publications
(48 reference statements)
0
1
0
Order By: Relevance
“…The authors concluded that sandbagging behavior can have a positive effect on others’ performance impressions, and sandbaggers may actively manipulate the environment for personal benefit. As found by Barnett et al (2018) , narcissists appear to engage in more sandbagging behavior which according to these authors may result from their fragile self-esteem and their hypersensitivity to evaluation. The question arises whether and to what extent strategic sandbagging overlaps with IP.…”
Section: The Impostor Phenomenonmentioning
confidence: 61%
“…The authors concluded that sandbagging behavior can have a positive effect on others’ performance impressions, and sandbaggers may actively manipulate the environment for personal benefit. As found by Barnett et al (2018) , narcissists appear to engage in more sandbagging behavior which according to these authors may result from their fragile self-esteem and their hypersensitivity to evaluation. The question arises whether and to what extent strategic sandbagging overlaps with IP.…”
Section: The Impostor Phenomenonmentioning
confidence: 61%
“…Researchers have discovered that dealing with oneself temperately, exaggeration and negative comparison increases the risk of dissatisfaction in individuals, such as self-criticism and unfit attitudes toward self-appearance which lowers self-esteem and increases symptoms of psychological dysfunction [39,40]. Self-compassion and self-improvement are also found to be inversely connected to shame and low self-esteem, based on cross-sectional data [41][42][43].…”
Section: Self-compassion and Appearance Comparisonmentioning
confidence: 99%